2015
DOI: 10.1007/s00394-015-1000-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in resting metabolic rate, respiratory quotient and body temperature: a comparison of Africans and European Australians

Abstract: In this study, SSA had a lower RMR, higher RQ and lower IET relative to EUR Australians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, adding feelings of connection to the regression model explained an additional 13.4% of the variance in oral temperature and this R 2 change was significant ( F (4, 49) = 3.51, p = .01). In other words, the association between oral temperature and feelings of connection held after controlling for sex, ethnicity, and BMI, factors known to alter oral temperature [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adding feelings of connection to the regression model explained an additional 13.4% of the variance in oral temperature and this R 2 change was significant ( F (4, 49) = 3.51, p = .01). In other words, the association between oral temperature and feelings of connection held after controlling for sex, ethnicity, and BMI, factors known to alter oral temperature [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between oral temperature and feelings of connection was tested first on its own and then controlling for other factors that are known to alter internal body temperature (i.e. sex, ethnicity, and BMI; [ 30 32 ]). A two stage hierarchical multiple regression was conducted with feelings of connection as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Today, most Hispanic Americans in Central America have some Native American genes, which might be associated with higher core temperatures. In contrast, Africans tend to have highly coupled mitochondria, with lower resting metabolic rates and lower core temperatures (1,30,31). Such data might provide an explanation for the conundrum that the epidemic may be greater among Hispanic Americans in Central America working the sugarcane fields as opposed to Hispanic Americans from Africa or the Caribbean, the latter having individuals with significant African ancestry (22).…”
Section: Introductionmentioning
confidence: 99%
“…This lowered metabolism has been linked to reduced NST and BAT activity [62]. A study has shown that even after adjusting for lean mass (muscle is more metabolically active), age, sex, and other potential confounders, African ancestry is associated with reduced basal metabolism and lower lipid oxidation compared with European ancestry [63]. Interestingly, this reduced basal metabolism has been identified in young African American women of normal weight and with no history of weight problems, suggesting a causal relationship in obesity [64].…”
Section: Energy Expenditure Variations By Ethnicitymentioning
confidence: 99%